Chapter 7 - Development of advanced nanocomposite membranes by molecular sieving nanomaterials (zeolite and MOF) - Dayang Norafizan, Awang Chee; Mohamed Afizal, Mohamed Amin; Farhana, Aziz; Juhana, Jaafar; Ahmad Fauzi, Ismail (Elsevier, 2020)
Zeolites and metal organic framework materials (MOFs) have many promising characteristics due to their chemical stability, abundant functionalities, and their molecular sieving properties. Consequently, studies on their fundamental properties have been studied for decades, from fabrication strategies to separation applications of zeolites and MOF-based membranes. This chapter provides an overview of different types of zeolites and MOF membranes, including strategies for their design and techniques of membrane preparation, and reviews progress in the area of gas and liquid separation, including pervaporation, wastewater treatment, and organic solvent nanofiltration.